A degradable film, preparation method and application as ground film

Hollow microspheres are prepared by hydrothermal reaction in polyterephthalate-adipate-butanediol ester and polylactic acid composite degradable films, and their mechanical properties and stability are improved through surface modification and grafting composite, which solves the compatibility, toughness and heat resistance of the film, and achieves higher impact resistance, tear resistance and degradation stability.

CN119286019BActive Publication Date: 2025-03-11SHANDONG LIZHUO SLEEP TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411817500.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-11
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

The existing polyterephthalate-adipate-butylene glycol terephthalate and polylactic acid composite degradable films have problems of poor compatibility, insufficient toughness and wear resistance, and the heat resistance stability in high-temperature environments needs to be improved.

Method used

Hollow microspheres were prepared by hydrothermal reactions using glucose, ethylene glycol, cetyl glucoside and citric acid, and the mechanical properties and stability of the microspheres were improved through surface modification and grafting composite. Then the composite hollow microspheres were combined with polyterephthalate-adipate-butylene glycol terephthalate-adipate-polylactic acid and polylactic acid to obtain a degradable film after plasma treatment.

Benefits of technology

The film's impact resistance, tear resistance, and degradation stability are improved, and the optical properties and water-retaining and breathable properties are synchronized, improving the film's stability in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The present invention provides a degradable film, a preparation method and an application as a ground film, belonging to the field of degradable films. The preparation method of the degradable film is composed of the following steps: preparing hollow microspheres, surface modification, grafting and compounding, preparing a film, and post-processing. The preparation method of the degradable film of the present invention can improve the compatibility, toughness and wear resistance of poly(butylene terephthalate-adipate-glycol) and polylactic acid, while improving the impact resistance, tear resistance and degradation stability of the degradable film, and synchronously adjust the optical properties and water-retaining and air-permeable properties of the degradable film; and further improve the stability of the degradable film in a high temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of degradable films, and in particular to a degradable film, a preparation method and an application thereof as a ground film. Background Art

[0002] The mulch film mulching cultivation technology is a new agricultural yield-increasing technology developed in the mid-20th century. The mulch film can make full use of the radiant heat of solar energy, increase the ground temperature and reduce the heat loss of the soil surface, increase the accumulated temperature in the mulch film, reduce water evaporation and block rainwater erosion, thereby playing a role in drought resistance and waterproofing; at the same time, the mulch film can also improve the physical and chemical properties of the soil, increase the activity of microorganisms in the soil, accelerate the decomposition of nutrients such as organic matter in the soil, improve the soil's ability to retain and supply fertilizers, give full play to the fertilizer effect, improve the growth environment of the soil arable layer, and promote the healthy growth of plants. Furthermore, the mulch film can also inhibit the growth of weeds and prevent animals such as rats, birds, and insects from harming seedlings or seeds, thereby achieving the effect of early sowing at the right time, uniform seedlings, complete seedlings, and strong seedlings, and achieving the effect of high and stable yields.

[0003] In traditional technology, ground film mostly uses non-degradable film materials, and the contradiction between the ecological and environmental crisis caused by it and people's ever-increasing green environmental protection and sustainable development concepts is becoming increasingly prominent. Biodegradable film generally refers to a polymer material that can be degraded into small molecules by microorganisms in the soil environment or water environment under natural conditions or other specific treatment conditions. Biodegradable film has similar effects as ordinary ground film materials, such as warming, drought resistance, evaporation reduction, salt inhibition, and waterproofing; at the same time, degradable ground film can be naturally degraded without the need for residual film recovery processes, effectively reducing the intensity of planting work; it can also reduce the residual film in farmland from the source and solve the problem of residual film pollution in farmland.

[0004] Polybutylene terephthalate-adipate-glycol / polylactic acid composite materials are representative biodegradable film materials currently used as ground films. Among them, polybutylene terephthalate-adipate-glycol is an aliphatic-aromatic copolyester with good flexibility and film-forming properties, and can be widely used in film materials; polylactic acid is a thermoplastic aliphatic polyester with good mechanical strength, processing properties and biodegradability.

[0005] However, the existing degradable films using polybutylene terephthalate-adipate-glycol and polylactic acid as main raw materials have the problems of poor compatibility, toughness and wear resistance of polybutylene terephthalate-adipate-glycol and polylactic acid. In order to overcome the above defects, the prior art usually adds auxiliary reinforcing components such as compatibilizers, chain extenders and inorganic fillers to the composite film materials of the two; however, the addition of the aforementioned auxiliary reinforcing components not only leads to the reduction of the impact resistance, tear resistance and degradation stability of the degradable film, but also affects the optical properties and water retention and air permeability of the degradable film.

[0006] Meanwhile, the heat resistance stability of the existing poly(butylene terephthalate-adipate-butylene terephthalate) and poly(lactic acid) composite biodegradable film in a high temperature environment needs to be further improved. Summary of the invention

[0007] In order to solve the technical problems existing in the prior art, the present invention provides a degradable film, a preparation method and an application as a ground film, which can improve the compatibility, toughness and wear resistance of poly(butylene terephthalate-adipate-glycol) and polylactic acid, while improving the impact resistance, tear resistance and degradation stability of the degradable film, and simultaneously adjust the optical properties and water-retaining and air-permeable properties of the degradable film; and further improve the stability of the degradable film in a high temperature environment.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0009] A method for preparing a degradable film comprises the following steps: preparing hollow microspheres, surface modification, grafting and compounding, preparing a film, and post-processing.

[0010] The method for preparing hollow microspheres comprises the following steps: putting glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water into a hydrothermal reactor, sealing the hydrothermal reactor, stirring for 20-30 minutes, controlling the hydrothermal reaction temperature to 250-260° C., the hydrothermal reaction pressure to 1.8-2.1 MPa, carrying out hydrothermal reaction for 1-1.5 hours with heat preservation and stirring, cooling to room temperature, centrifuging at 10000-11000 rpm to obtain a microsphere precursor, washing the microsphere precursor with deionized water, placing the precursor in a metal basket in a steam explosion reactor, sealing the steam explosion reactor, introducing water vapor, controlling the temperature in the steam explosion reactor to 220-230° C., keeping the temperature for 10-20 minutes, releasing the pressure and obtaining a steam explosion product; and drying the steam explosion product in a constant temperature drying oven at 105-115° C. to a constant weight to obtain hollow microspheres.

[0011] In the preparation of the hollow microspheres, the weight ratio of glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water is 10-11:7-7.5:2-2.5:3-3.5:55-60.

[0012] The surface modification method comprises the following steps: adding a hydrogen peroxide solution with a mass concentration of 5-6wt% and hollow microspheres into a reaction kettle, stirring for 10-20min, heating to 90-95°C at a heating rate of 1-2°C / min, preserving, stirring and refluxing for 2-3h, and centrifuging at 12000-13000rpm to obtain a solid; washing the solid 2-3 times with 5-6 times the weight of deionized water, transferring the solid into a constant temperature drying oven, and drying at 105-115°C to a constant weight to obtain the modified hollow microspheres.

[0013] In the surface modification, the weight ratio of the hydrogen peroxide solution to the hollow microspheres is 6-8:1.

[0014] The grafting composite method comprises the following steps: adding the modified hollow microspheres and anhydrous ethanol into a reaction kettle, stirring for 10-20 minutes, then continuously adding polytetrahydrofuran diol and methyl methacrylate, stirring and heating to 50-55° C., and keeping the temperature; then stirring and adding azobisisobutyronitrile, stirring at 30-40 rpm, keeping the temperature and stirring for 8-10 hours, centrifuging at 9000-10000 rpm to obtain a solid, washing the solid with deionized water, transferring the solid into a vacuum drying oven, and drying at 80-85° C. for 11-12 hours in a vacuum environment of 0.05-0.06 MPa to obtain a composite hollow microsphere.

[0015] In the graft composite, the weight ratio of the modified hollow microspheres, anhydrous ethanol, polytetrahydrofuran diol, methyl methacrylate and azobisisobutyronitrile is 9-9.5:100-105:6-6.5:12.5-13:0.8-0.9.

[0016] The method for preparing the film comprises the following steps: adding polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleyl titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch and sodium carboxymethyl cellulose into a high-speed mixer, mixing them evenly to obtain a premix; then adding the premix into a twin-screw extruder, controlling the temperature of the twin-screw extruder to be 120-130° C., extruding and granulating to obtain a granular material; then adding the granular material into a film blowing machine, controlling the temperature of the first stage of the film blowing machine to be 130-135° C., the temperature of the second stage to be 135-140° C., the temperature of the third stage to be 135-140° C. and the temperature of the die head to be 140-145° C., performing film blowing treatment to obtain a composite film with a thickness of 70-90 μm.

[0017] In the film preparation, the weight ratio of polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose is 100:7-8:6-6.5:0.4-0.5:0.9-1:1.6-1.7:1.7-2:2-2.2.

[0018] The post-treatment method is as follows: placing the composite film in a processing chamber of a low-temperature plasma device, completely replacing the air in the processing chamber with nitrogen, introducing a mixed gas of ammonia and argon, controlling the low-temperature plasma treatment frequency to 10-11 MHz, the treatment power to 200-250 W, and performing low-temperature plasma treatment on the composite film for 5-10 minutes to obtain a degradable film.

[0019] In the post-treatment, the volume ratio of ammonia gas to argon gas is 2-2.3:1.

[0020] A degradable film is prepared by the above-mentioned preparation method.

[0021] An application of the aforementioned degradable film as a ground film.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) In the preparation method of the degradable film of the present invention, glucose, ethylene glycol, cetearyl glucoside and citric acid are used to carry out a hydrothermal reaction. In this process, cetearyl glucoside is used as a crystal nucleus, and ethylene glycol and glucose are deposited and coated on its outer layer to form a shell layer. In a hydrothermal high-temperature environment, cetearyl glucoside is pyrolyzed to form a hollow structure, and the ethylene glycol and glucose in the shell layer are carbonized to form a porous shell layer to obtain a microsphere precursor; then the microsphere precursor is kept in a high-temperature steam environment and kept still for a secondary carbonization process to further improve the mechanical properties, thermal stability and stability of the hollow microspheres in the degradable film, and then the pore structure is adjusted by steam explosion to obtain hollow microspheres. Then, in the surface modification step, the hollow microspheres are surface modified by a hydrogen peroxide solution, which further ensures the grafting composite performance of the modified hollow microspheres with polytetrahydrofuran diol and methyl methacrylate in the subsequent grafting composite step, and further improves its stability in the degradable film. Then in the grafting and compounding step, polytetrahydrofuran diol and methyl methacrylate are used to carry out grafting and compounding on the surface of the modified hollow microspheres to obtain composite hollow microspheres with polymer brushes; then in the film preparation step, composite hollow microspheres, isopropyl trioleyl titanate, silane coupling agent KH-550, and acetyl citrate tributyl are used in combination with polybutylene terephthalate-adipate and polylactic acid to prepare a composite film, and the composite film is subjected to plasma treatment to obtain a degradable film; wherein, by using composite hollow microspheres to compound polybutylene terephthalate-adipate and polylactic acid, the bonding performance of polytetrahydrofuran diol, methyl methacrylate grafted on the surface of the microspheres is improved, and the toughness, wear resistance, impact resistance, tear resistance and high temperature stability of the degradable film are further improved; and by using the hollow microspheres to compound the composite hollow microspheres with polybutylene terephthalate-adipate and polylactic acid, the bonding performance of polytetrahydrofuran diol, methyl methacrylate grafted on the surface of the microspheres is improved, and the toughness, wear resistance, impact resistance, tear resistance and high temperature stability of the degradable film are further improved. The scattering effect of the hollow microspheres on light can further regulate the optical properties and water-retaining and air-permeable properties of the film, which is beneficial to provide a suitable growth environment for crops when the film is subsequently used as a mulch film; at the same time, during the degradation process of the film, the hollow pores of the hollow microspheres can improve the adhesion and contact between microorganisms and the film, thereby improving the degradation stability of the film; the raw materials in the film preparation steps cooperate with each other, which can improve the compatibility, toughness and wear resistance of poly(butylene terephthalate-adipate-glycol) and polylactic acid, while improving the impact resistance, tear resistance and degradation stability of the degradable film, and simultaneously regulate the optical properties and water-retaining and air-permeable properties of the degradable film; and further improve the stability of the degradable film in a high temperature environment; further, through low-temperature plasma treatment of the composite film in post-treatment, the water-retaining and air-permeable properties of the film can be further regulated, thereby improving its application performance as a mulch film.

[0024] (2) The tensile strength of the degradable film of the present invention is 35.5-35.8 MPa, the elongation at break is 600-606%, and the impact strength is 36.9-37.1 KJ / m 2 The tear strength is 22.1-22.5KN / m, the transmittance is 89.1-89.3%, and the haze is 36.4-36.6%.

[0025] (3) After a load block weighing 150 g was reciprocated on the same side surface of the degradable film of the present invention for 100 times, the light transmittance attenuation rate was 2.5-2.7%, indicating that the degradable film has good wear resistance.

[0026] (4) The oxygen permeability coefficient of the degradable film of the present invention is (120.0-120.4)×10 -15 (cm 3 cm) / (cm 2 ·s·Pa), and the water vapor permeability coefficient is (5.0-5.1)×10 -11 (g·cm) / (cm 2 ·s·Pa).

[0027] (5) After standing for 72 hours in an environment at a temperature of 55°C, the degradable film of the present invention still has a tensile strength of 35.5MPa, an elongation at break of 601%, and an impact strength of 37.0KJ / m 2 , the tear strength can still reach 22.3KN / m, the light transmittance is 89.2%, and the haze is 36.8%.

[0028] (6) During the soil covering degradation process of the degradable film of the present invention, the degradation rate was 8.7% at the 11th week and 97.2% at the 24th week; the degradation rate of the degradable film was slow in the early stage, which could effectively maintain its protective effect on crops when used as a ground film; the degradation rate was faster in the later stage and the degradation rate was high. DETAILED DESCRIPTION

[0029] In order to have a clearer understanding of the technical features, purposes and effects of the present invention, the specific implementation methods of the present invention are now described.

[0030] Example 1

[0031] This embodiment provides a method for preparing a degradable film, and the specific steps are as follows:

[0032] 1. Preparation of hollow microspheres

[0033] Glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water are put into a hydrothermal reactor, and after the hydrothermal reactor is sealed, it is stirred for 20 minutes, the hydrothermal reaction temperature is controlled to be 250°C, the hydrothermal reaction pressure is controlled to be 1.8 MPa, and the hydrothermal reaction is carried out for 1 hour with insulation and stirring, and then cooled to room temperature, and centrifuged at 10000 rpm to obtain a microsphere precursor, and the microsphere precursor is washed with deionized water, and then placed in a metal basket in a steam explosion reactor, and after the steam explosion reactor is sealed, water vapor is introduced, and the temperature in the steam explosion reactor is controlled to be 220°C. After insulation for 10 minutes, the pressure is released to obtain a steam explosion product; the steam explosion product is dried to constant weight at 105°C in a constant temperature drying oven to obtain hollow microspheres.

[0034] Wherein, the weight ratio of glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water is 10:7:2:3:55.

[0035] 2. Surface modification

[0036] A 5wt% hydrogen peroxide solution and hollow microspheres were put into a reactor, stirred for 10 minutes, and then heated to 90°C at a heating rate of 1°C / min. After being kept warm and stirred at reflux for 2 hours, solids were obtained by centrifugation at 12000rpm. The solids were washed twice with 5 times the weight of deionized water, transferred to a constant temperature drying oven, and dried at 105°C to constant weight to obtain modified hollow microspheres.

[0037] Wherein, the weight ratio of hydrogen peroxide solution to hollow microspheres is 6:1.

[0038] 3. Grafting

[0039] The modified hollow microspheres and anhydrous ethanol were added into a reactor, stirred for 10 minutes, and then polytetrahydrofuran diol and methyl methacrylate were added, stirred and heated to 50°C, and kept warm; then azobisisobutyronitrile was added with stirring, and the mixture was stirred and reacted for 8 hours at 30 rpm, and then centrifuged at 9000 rpm to obtain a solid. After the solid was washed with deionized water, it was transferred to a vacuum drying oven and dried at 80°C for 11 hours in a vacuum environment of 0.05 MPa to obtain a composite hollow microsphere.

[0040] Wherein, the weight ratio of modified hollow microspheres, anhydrous ethanol, polytetramethylene glycol, methyl methacrylate and azobisisobutyronitrile is 9:100:6:12.5:0.8.

[0041] 4. Preparation of thin film

[0042] Polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose are put into a high-speed mixer and mixed evenly to obtain a premix; the premix is ​​then put into a twin-screw extruder, the temperature of the twin-screw extruder is controlled to be 120° C., extrusion granulation is performed to obtain a granular material; the granular material is then put into a film blowing machine, the temperature of the first stage of the film blowing machine is controlled to be 130° C., the temperature of the second stage is controlled to be 135° C., the temperature of the third stage is controlled to be 135° C., and the temperature of the die head is controlled to be 140° C., and a film blowing process is performed to obtain a composite film with a thickness of 85 μm.

[0043] Among them, the weight ratio of polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose is 100:7:6:0.4:0.9:1.6:1.7:2.

[0044] The method used in this embodiment

[0045] 5. Post-processing

[0046] The composite film was placed in a processing chamber of a low-temperature plasma device. After nitrogen was used to completely replace the air in the processing chamber, a mixed gas of ammonia and argon was introduced. The low-temperature plasma processing frequency was controlled to 10 MHz and the processing power was 200 W. The composite film was subjected to low-temperature plasma treatment for 5 minutes to obtain a degradable film.

[0047] The volume ratio of ammonia to argon is 2:1.

[0048] This embodiment also provides a degradable film prepared by the aforementioned method.

[0049] This embodiment also provides the application of the aforementioned degradable film as a ground film.

[0050] Example 2

[0051] This embodiment provides a method for preparing a degradable film, and the specific steps are as follows:

[0052] 1. Preparation of hollow microspheres

[0053] Glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water were put into a hydrothermal reactor, and the reactor was sealed and stirred for 25 minutes. The hydrothermal reaction temperature was controlled to be 255°C, the hydrothermal reaction pressure was controlled to be 2MPa, and the hydrothermal reaction was carried out for 1.3 hours with insulation and stirring, and then cooled to room temperature, and centrifuged at 11000rpm to obtain a microsphere precursor. The microsphere precursor was washed with deionized water and placed in a metal basket in a steam explosion reactor. After the steam explosion reactor was sealed, water vapor was introduced, and the temperature in the steam explosion reactor was controlled to be 225°C. After insulation for 15 minutes, the pressure was released to obtain a steam explosion product; the steam explosion product was dried to constant weight at 110°C in a constant temperature drying oven to obtain hollow microspheres.

[0054] Among them, the weight ratio of glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water is 10.5:7.3:2.2:3.2:57.

[0055] 2. Surface modification

[0056] A hydrogen peroxide solution with a mass concentration of 5.7wt% and hollow microspheres were put into a reactor, stirred for 15 minutes, and then heated to 92°C at a heating rate of 1.5°C / min. After being kept warm and stirred and refluxed for 2.5 hours, solids were obtained by centrifugation at 13000rpm; the solids were washed three times with 5.5 times the weight of deionized water, transferred to a constant temperature drying oven, and dried at 110°C to constant weight to obtain modified hollow microspheres.

[0057] Wherein, the weight ratio of hydrogen peroxide solution to hollow microspheres is 7:1.

[0058] 3. Grafting

[0059] The modified hollow microspheres and anhydrous ethanol were added into a reactor, stirred for 15 minutes, and then polytetrahydrofuran diol and methyl methacrylate were added, stirred and heated to 52°C, and kept warm; then azobisisobutyronitrile was added with stirring, and the reaction was kept warm and stirred at 35 rpm for 9 hours, and then the solid was obtained by centrifugation at 10000 rpm. After the solid was washed with deionized water, it was transferred to a vacuum drying oven and dried at 82°C for 12 hours in a vacuum environment of 0.055 MPa to obtain composite hollow microspheres.

[0060] Among them, the weight ratio of modified hollow microspheres, anhydrous ethanol, polytetramethylene glycol, methyl methacrylate and azobisisobutyronitrile is 9.3:102:6.2:12.7:0.85.

[0061] 4. Preparation of thin film

[0062] Polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleyl titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose are put into a high-speed mixer and mixed evenly to obtain a premix; the premix is ​​then put into a twin-screw extruder, the temperature of the twin-screw extruder is controlled to be 125° C., and granulation is performed by extrusion to obtain a granular material; the granular material is then put into a film blowing machine, the temperature of the first stage of the film blowing machine is controlled to be 132° C., the temperature of the second stage is controlled to be 137° C., the temperature of the third stage is controlled to be 140° C., and the temperature of the die head is controlled to be 143° C., and a film blowing process is performed to obtain a composite film with a thickness of 85 μm.

[0063] Among them, the weight ratio of polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose is 100:7.5:6.3:0.45:0.95:1.66:1.9:2.1.

[0064] 5. Post-processing

[0065] The composite film was placed in a processing chamber of a low-temperature plasma device. After nitrogen was used to completely replace the air in the processing chamber, a mixed gas of ammonia and argon was introduced. The low-temperature plasma processing frequency was controlled to 10.5 MHz and the processing power was 220 W. The composite film was subjected to low-temperature plasma treatment for 7 minutes to obtain a degradable film.

[0066] The volume ratio of ammonia to argon is 2.1:1.

[0067] This embodiment also provides a degradable film prepared by the aforementioned method.

[0068] This embodiment also provides the application of the aforementioned degradable film as a ground film.

[0069] Example 3

[0070] This embodiment provides a method for preparing a degradable film, and the specific steps are as follows:

[0071] 1. Preparation of hollow microspheres

[0072] Glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water are put into a hydrothermal reactor, and after the hydrothermal reactor is sealed, it is stirred for 30 minutes, the hydrothermal reaction temperature is controlled to be 260°C, the hydrothermal reaction pressure is controlled to be 2.1 MPa, and the hydrothermal reaction is carried out for 1.5 hours with insulation and stirring, and then cooled to room temperature, and centrifuged at 11000rpm to obtain a microsphere precursor. After washing the microsphere precursor with deionized water, it is placed in a metal basket in a steam explosion reactor, and after the steam explosion reactor is sealed, water vapor is introduced, and the temperature in the steam explosion reactor is controlled to be 230°C. After insulation for 20 minutes, the pressure is released to obtain a steam explosion product; the steam explosion product is dried at 115°C in a constant temperature drying oven to constant weight to obtain hollow microspheres.

[0073] Wherein, the weight ratio of glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water is 11:7.5:2.5:3.5:60.

[0074] 2. Surface modification

[0075] A 6wt% hydrogen peroxide solution and hollow microspheres were put into a reactor, stirred for 20 minutes, and then heated to 95°C at a heating rate of 2°C / min. After being kept warm and stirred at reflux for 3 hours, solids were obtained by centrifugation at 13000rpm. The solids were washed three times with 6 times the weight of deionized water, transferred to a constant temperature drying oven, and dried at 115°C to constant weight to obtain modified hollow microspheres.

[0076] Wherein, the weight ratio of hydrogen peroxide solution to hollow microspheres is 8:1.

[0077] 3. Grafting

[0078] The modified hollow microspheres and anhydrous ethanol were added into a reactor, stirred for 20 minutes, and then polytetrahydrofuran diol and methyl methacrylate were added, stirred and heated to 55°C, and kept warm; then azobisisobutyronitrile was added with stirring, and the mixture was stirred and reacted for 10 hours at 40 rpm, and then centrifuged at 10000 rpm to obtain a solid. After the solid was washed with deionized water, it was transferred to a vacuum drying oven and dried at 85°C for 12 hours in a vacuum environment of 0.06 MPa to obtain composite hollow microspheres.

[0079] Wherein, the weight ratio of modified hollow microspheres, anhydrous ethanol, polytetrahydrofuran diol, methyl methacrylate and azobisisobutyronitrile is 9.5:105:6.5:13:0.9.

[0080] 4. Preparation of thin film

[0081] Polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleyl titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose are put into a high-speed mixer and mixed evenly to obtain a premix; the premix is ​​then put into a twin-screw extruder, the temperature of the twin-screw extruder is controlled to be 130° C., extrusion granulation is performed to obtain a granular material; the granular material is then put into a film blowing machine, the temperature of the first stage of the film blowing machine is controlled to be 135° C., the temperature of the second stage is controlled to be 140° C., the temperature of the third stage is controlled to be 140° C., and the temperature of the die head is controlled to be 145° C., and a film blowing process is performed to obtain a composite film with a thickness of 85 μm.

[0082] Among them, the weight ratio of polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose is 100:7:6:0.4:0.9:1.6:1.7:2.

[0083] 5. Post-processing

[0084] The composite film was placed in a processing chamber of a low-temperature plasma device. After nitrogen was used to completely replace the air in the processing chamber, a mixed gas of ammonia and argon was introduced. The low-temperature plasma processing frequency was controlled to 11 MHz and the processing power was 250 W. The composite film was subjected to low-temperature plasma treatment for 10 minutes to obtain a degradable film.

[0085] The volume ratio of ammonia to argon is 2.3:1.

[0086] This embodiment also provides a degradable film prepared by the aforementioned method.

[0087] This embodiment also provides the application of the aforementioned degradable film as a ground film.

[0088] Comparative Example 1

[0089] The technical solution of Example 2 is adopted, but the differences are: 1) in the step of preparing hollow microspheres, ethylene glycol, cetearyl glucoside and steam explosion treatment are omitted; 2) the surface modification step is omitted.

[0090] Comparative Example 2

[0091] The technical solution of Example 2 is adopted, but the differences are: 1) nano-activated carbon particles are used instead of hollow microspheres in the surface modification step; 2) the grafting composite step is omitted.

[0092] The tensile strength, elongation at break, impact strength, tear strength, light transmittance, and haze of the degradable films of Examples 1-3 and Comparative Examples 1-2 were tested respectively. The tensile strength and elongation were tested in accordance with the reference standard GB / T1040.3-2006, the impact strength was tested in accordance with the reference standard GB / T 8809-2015, the tear strength was tested in accordance with the reference standard GB / T16578.1-2008, and the light transmittance and haze were tested in accordance with the reference standard GB / T2410-2008. The specific test results are shown in the following table:

[0093]

[0094] Furthermore, the wear resistance test was performed on the degradable films of Examples 1-3 and Comparative Examples 1-2. Specifically, a load block weighing 150 g was placed on the same side surface of the degradable film for reciprocating motion, and the reciprocating motion distance was controlled to be 20 cm. After 100 reciprocating motions, the light transmittance of the reciprocating motion area on the degradable films of Examples 1-3 and Comparative Examples 1-2 was tested, the light transmittance after friction was obtained, and then the light transmittance attenuation rate of each degradable film was calculated.

[0095] The calculation method of the light transmittance attenuation rate is: [(light transmittance before friction-light transmittance after friction) / light transmittance before friction]×100%.

[0096] The specific test results are shown in the following table:

[0097]

[0098] Furthermore, the oxygen permeability coefficient and the water vapor permeability coefficient of the degradable films of Examples 1-3 and Comparative Examples 1-2 were tested respectively.

[0099] Among them, the detection method of oxygen permeability coefficient is to cut each degradable film into samples with a diameter of 90 mm, place them in a plastic permeability tester, control the test temperature to 20°C, and the oxygen source pressure to 0.5MPa, and detect the oxygen permeability coefficient of each sample.

[0100] The method for testing the water vapor permeability coefficient is to cut each degradable film into samples with a diameter of 80 mm, place them in a plastic water vapor permeability tester, control the test temperature to 25°C and the relative humidity to 53%, and test the water vapor permeability coefficient of each sample.

[0101] The specific test results are shown in the following table:

[0102]

[0103] Furthermore, the degradable films of Example 2 and Comparative Examples 1-2 were placed in an environment at a temperature of 55° C. and left to stand for 72 hours. The tensile strength, elongation at break, impact strength, tear strength, light transmittance and haze of each degradable film were tested. The specific test results are shown in the following table:

[0104]

[0105] Furthermore, the degradable films of Example 2 and Comparative Examples 1-2 were subjected to degradation tests. Specifically, the surface of each degradable film was completely covered with soil with a thickness of 2 cm, and water was sprayed during the degradation test to keep the soil moisture not less than 35%. In the 11th week and the 24th week of the degradation test, the soil was sprayed with water per unit area (100 cm 2 ) Take samples of the remaining degradable film in the soil and determine the degradation rate.

[0106] The calculation method of the degradation rate is: [(film weight per unit area before degradation - film weight per unit area after degradation) / film weight per unit area before degradation] × 100%.

[0107] The specific test results are shown in the following table:

[0108]

[0109] It can be seen that in the preparation method of the degradable film of the present invention, glucose, ethylene glycol, cetearyl glucoside and citric acid are used to carry out hydrothermal reaction. In this process, cetearyl glucoside is used as the crystal nucleus, ethylene glycol and glucose are deposited and coated on its outer layer to form a shell layer. In a hydrothermal high temperature environment, cetearyl glucoside is pyrolyzed to form a hollow structure, and the ethylene glycol and glucose of the shell layer are carbonized to form a porous shell layer to obtain a microsphere precursor; then the microsphere precursor is kept in a high temperature steam environment and kept still for a secondary carbonization process to further improve the mechanical properties, thermal stability and stability of the hollow microspheres in use in the degradable film, and then the pore structure is adjusted by steam explosion to obtain hollow microspheres. Then in the surface modification step, the hollow microspheres are surface modified by a hydrogen peroxide solution, which further ensures the grafting composite performance of the modified hollow microspheres with polytetrahydrofuran diol and methyl methacrylate in the subsequent grafting composite step, and further improves its stability in the degradable film. Then in the grafting and compounding step, polytetrahydrofuran diol and methyl methacrylate are used to carry out grafting and compounding on the surface of the modified hollow microspheres to obtain composite hollow microspheres with polymer brushes; then in the film preparation step, composite hollow microspheres, isopropyl trioleyl titanate, silane coupling agent KH-550, and acetyl citrate tributyl are used in combination with polybutylene terephthalate-adipate and polylactic acid to prepare a composite film, and the composite film is subjected to plasma treatment to obtain a degradable film; wherein, by using composite hollow microspheres to compound polybutylene terephthalate-adipate and polylactic acid, the bonding performance of polytetrahydrofuran diol, methyl methacrylate grafted on the surface of the microspheres is improved, and the toughness, wear resistance, impact resistance, tear resistance and high temperature stability of the degradable film are further improved; and by using the hollow microspheres to compound the composite hollow microspheres with polybutylene terephthalate-adipate and polylactic acid, the bonding performance of polytetrahydrofuran diol, methyl methacrylate grafted on the surface of the microspheres is improved, and the toughness, wear resistance, impact resistance, tear resistance and high temperature stability of the degradable film are further improved. The scattering effect of the hollow microspheres on light can further regulate the optical properties and water-retaining and air-permeable properties of the film, which is beneficial to provide a suitable growth environment for crops when the film is subsequently used as a mulch film; at the same time, during the degradation process of the film, the hollow pores of the hollow microspheres can improve the adhesion and contact between microorganisms and the film, thereby improving the degradation stability of the film; the raw materials in the film preparation steps cooperate with each other, which can improve the compatibility, toughness and wear resistance of poly(butylene terephthalate-adipate-glycol) and polylactic acid, while improving the impact resistance, tear resistance and degradation stability of the degradable film, and simultaneously regulate the optical properties and water-retaining and air-permeable properties of the degradable film; and further improve the stability of the degradable film in a high temperature environment; further, through low-temperature plasma treatment of the composite film in post-treatment, the water-retaining and air-permeable properties of the film can be further regulated, thereby improving its application performance as a mulch film.

[0110] Unless otherwise specified, all percentages used in the present invention are by mass.

[0111] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a degradable film, characterized in that: The method comprises the following steps: preparing hollow microspheres, surface modification, grafting and compounding, preparing thin films, and post-treatment; The method for preparing hollow microspheres comprises the following steps: uniformly mixing glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water, controlling the hydrothermal reaction temperature to be 250-260° C., the hydrothermal reaction pressure to be 1.8-2.1 MPa, and performing a hydrothermal reaction, separating and obtaining a microsphere precursor; placing the microsphere precursor in a steam explosion kettle, introducing water vapor, controlling the temperature in the steam explosion kettle to be 220-230° C., keeping the temperature and standing, and then releasing the pressure to obtain a steam explosion product; and drying the steam explosion product to obtain hollow microspheres; The surface modification method comprises mixing the hollow microspheres and the hydrogen peroxide solution uniformly, heating, stirring and refluxing, separating and obtaining a solid, and washing and drying the solid to obtain the modified hollow microspheres; The grafting composite method comprises: mixing the modified hollow microspheres, anhydrous ethanol, polytetrahydrofuran diol and methyl methacrylate, heating to 50-55° C., keeping the temperature, adding azobisisobutyronitrile, keeping the temperature and stirring for reaction, separating and obtaining solids, washing and vacuum drying the solids, and obtaining composite hollow microspheres; The method for preparing the film comprises: uniformly mixing polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose, and performing extrusion granulation and film blowing to obtain a composite film; The post-treatment method is that the composite film is treated with low-temperature plasma in a mixed atmosphere of ammonia and argon to obtain a degradable film.

2. The method for preparing a degradable film according to claim 1, characterized in that: In the preparation of the hollow microspheres, the hydrothermal reaction time is 1-1.5h; The microsphere precursor is kept at 220-230°C in the steam explosion kettle for 10-20 minutes; The weight ratio of glucose, ethylene glycol, cetearyl glucoside, citric acid and deionized water is 10-11:7-7.5:2-2.5:3-3.5:55-60.

3. The method for preparing a degradable film according to claim 1, characterized in that: In the surface modification, the heating, stirring and reflux temperature is 90-95° C., the heating rate is 1-2° C. / min, and the heating, stirring and reflux time is 2-3 h.

4. The method for preparing a degradable film according to claim 1, characterized in that: In the surface modification, the mass concentration of the hydrogen peroxide solution is 5-6wt%; The weight ratio of the hydrogen peroxide solution to the hollow microspheres is 6-8:

1.

5. The method for preparing a degradable film according to claim 1, characterized in that: In the grafting and compounding, the heat preservation and stirring reaction time is 8-10 hours, and the stirring speed is 30-40rpm; The weight ratio of the modified hollow microspheres, anhydrous ethanol, polytetrahydrofuran diol, methyl methacrylate and azobisisobutyronitrile is 9-9.5:100-105:6-6.5:12.5-13:0.8-0.

9.

6. The method for preparing a degradable film according to claim 1, characterized in that: In the film preparation, the weight ratio of polybutylene terephthalate-adipate, polylactic acid, composite hollow microspheres, isopropyl trioleate acyloxy titanate, silane coupling agent KH-550, acetyl tributyl citrate, PBAT degradation masterbatch, and sodium carboxymethyl cellulose is 100:7-8:6-6.5:0.4-0.5:0.9-1:1.6-1.7:1.7-2:2-2.

2.

7. The method for preparing a degradable film according to claim 1, characterized in that: In the film preparation, the extrusion granulation temperature is 120-130°C; In the film blowing process, the first stage temperature of the film blowing machine is controlled to be 130-135°C, the second stage temperature is 135-140°C, the third stage temperature is 135-140°C, and the die head temperature is 140-145°C; The thickness of the composite film is 70-90 μm.

8. The method for preparing a degradable film according to claim 1, characterized in that: In the post-treatment, the volume ratio of ammonia to argon is 2-2.3:1; The low-temperature plasma treatment frequency is 10-11 MHz, the treatment power is 200-250 W, and the treatment time is 5-10 min.

9. A degradable film, characterized in that: The method is prepared by the method according to any one of claims 1 to 8.

10. Use of the degradable film according to claim 9 as a ground film.

Citation Information

Patent Citations

  • Special strengthening, toughening and transmittance increasing master batch for ultrathin fully-biodegradable mulch film

    CN107365482A

  • Degradable material with heat insulation and energy storage performance and preparation method thereof

    CN114989588A